Clinical performance and accuracy of a qPCR-based SARS-CoV-2 mass-screening workflow for healthcare-worker surveillance using pooled self-sampled gargling solutions: A cross-sectional study. Issue 5 (November 2021) - Olearo, Flaminia; Nörz, Dominik; Hoffman, Armin; Grunwald, Moritz; Gatzemeyer, Kimani; Christner, Martin; Both, Anna; Campos, Cristina Elena Belmar; Braun, Platon; Andersen, Gabriele; Pfefferle, Susanne; Zapf, Antonia; et al.
Highlights: Establishment of a self-sampled gargling solution for SARS-CoV-2 surveillance by qPCR. Automated sample-pooling conserved qPCR reagents and reduced costs. The workflow was used in a mass-screening program for healthcare-workers (HCW). High efficiency in detecting (asymptomatically) infected HCWs. Summary: Introduction: The large number of asymptomatic SARS-CoV-2 infections necessitates general screening of employees. We evaluate the performance of a SARS-CoV-2 screening program in asymptomatic healthcare-workers (HCW), utilizing self-sampled gargling-solution and sample pooling for RT-qPCR. Methods: We conducted a cross-sectional retrospective study to collect real-life data on the performance of a screening-workflow based on automated-pooling and high-throughput qPCR testing over a 3-month-period at the University Hospital Hamburg. Results: Matrix validation reveals that lower limit of detection for SARS-CoV-2 RNA in gargling-solution was 180 copies/mL (5-sample-pool). A total of 55, 122 self-collected gargle samples (= 7513 HCWs) was analyzed. The median time to result was 8.5 hours (IQR 7.2–10.8). Of 11, 192 pools analyzed, 11, 041 (98.7%) were negative, 69 (0.6%) were positive and 82 (0.7%) were invalid. Individual testing of pool participants revealed 57 SARS-CoV-2 previously unrecognized infections. All 57 HCWs were either pre-symptomatic or asymptomatic (prevalence 0.76%, CI95%0.58–0.98%). Accuracy based on HCWs with gargle-solution and NP-swab available within 3-day-interval ( N  = 521) was 99.5% (CI95%98.3–99.9%), sensitivity 88.9% (CI95%65.3–98.6%) while specificity 99.8% (CI95%98.9–99.9). Conclusion: This workflow was highly effective in identifying SARS-CoV-2 positive HCWs, thereby lowering the potential of inter-HCW and HCW-patient transmissions. Automated-sample-pooling helped to conserve qPCR reagents and represents a promising alternative strategy to antigen testing in mass-screening programs.